Pengaruh Pendidikan Kesehatan Menggunakan Audio Visual terhadap Perilaku Oral Hygine pada Murid di SD Negeri 7 Bukit Tunggal Palangka Raya: The Effect of Health Education Using Audio Visual on Oral Hygine Behavior in Student at SD Negeri 7 Bukit Tunggal Palangka Raya - Vita Natalia; Rizki Muji Lestari; Evy Kasanova; Victorius Victorius (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Background: Oral hygiene is a common way to clem any oral hygiene attached to the surface of the teeth and gums. Oral hygiene at the optimal time, like after eating in the morning and before bed at night. Phenomena that occur in grade SD Negeri 7 Bukit Tunggal Raya are still many students who don’t understand good and right oral hygiene and lack awareness of oral hygiene. Research Purpose: Analyze the effect of health education on oral hygiene behavior in students in grades 7 Bukit Tunggal Palangka Raya public elementary school in 2019. Research Method: Design this research is pre-experimental with a